2021
DOI: 10.1097/jcma.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic therapeutic effect of low-dose bevacizumab with cisplatin-based chemotherapy for advanced or recurrent cervical cancer

Abstract: Background: Cisplatin-based chemotherapy (CBC) is highly efficacious for advanced cervical cancer; its efficacy can be enhanced by combining with 15 mg/kg (standard dose) bevacizumab (BEV). However, this standard dose is associated with various adverse events (AEs). Therefore, in this retrospective study, we analyzed the survival outcomes and AEs in patients with advanced or recurrent cervical cancer treated with CBC in combination with BEV 7.5 mg/kg. Methods: Registered patient data were retrieved between O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Metformin, an AMPK activator, is considered the first-line agent for pre-DM and DM, except for those patients with poor estimated glomerular filtration rate (<30 mL/min). 30,33,36,60,112,[117][118][119][120] Unfortunately, there are several RCTs that failed to support the effectiveness of metformin in the prevention and treatment of MAFLD, suggesting no improvement in MASH stages in patients treated with metformin. 101,112,116,117 By contrast, reports suggested that the use of metformin may decrease the risk of developing HCC (hazard ratio [HR], 0.25) in MAFLD as well as decrease the overall mortality of patients with liver cirrhosis and DM (HR, 0.42).…”
Section: Strategy For Targeting Dm and Mafld Simultaneously: Adamentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, an AMPK activator, is considered the first-line agent for pre-DM and DM, except for those patients with poor estimated glomerular filtration rate (<30 mL/min). 30,33,36,60,112,[117][118][119][120] Unfortunately, there are several RCTs that failed to support the effectiveness of metformin in the prevention and treatment of MAFLD, suggesting no improvement in MASH stages in patients treated with metformin. 101,112,116,117 By contrast, reports suggested that the use of metformin may decrease the risk of developing HCC (hazard ratio [HR], 0.25) in MAFLD as well as decrease the overall mortality of patients with liver cirrhosis and DM (HR, 0.42).…”
Section: Strategy For Targeting Dm and Mafld Simultaneously: Adamentioning
confidence: 99%
“…25,26 There are many strategies applicable to DM control, such as lifestyle modification, routine and continuous blood glucose monitoring, and pharmacological therapy (antidiabetic agents [ADA] and sugar-lowering drugs), 27–30 and all of them attempt to minimize DM-related adverse events (AEs) and maintain the quality of life, similar to the therapy for other troublesome diseases by multiple modality strategy. 31–33…”
Section: Introductionmentioning
confidence: 99%
“…These abnormal areas of tissue may become cancerous. Numerous studies have demonstrated that angiogenesis and the vascularity of cervical cancer correlate with the individual tumor characteristics and prognostic factors for recurrence [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A big congratulation is given to Dr. Li-Chun Liu as the 2021 Journal of the Chinese Medical Association Outstanding Research Paper Award winner who is selected from all authors having contributed their research works to the Journal of the Chinese Medical Association (JCMA) last year. [1][2][3][4][5][6] This year's award, sponsored by the Chinese Medical Association-Taipei (CMA-Taipei), is granted to researchers who demonstrate their excellent performance and great contribution to enhanced better patients' care. Dr. Liu won this credit at the Annual Meeting of the CMA-Taipei on July 16, 2022, held at Taipei, Taiwan, and the meeting is still affected apparently by the emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (coronavirus disease 2019 [COVID-19]) pandemic.…”
mentioning
confidence: 99%